Erastin-induced multi-pathway cell death in endometriosis: a mechanistic and translational narrative review - Gao, Zhe; Du, Juan (Frontiers in Medicine, 2025)
This narrative review examines the therapeutic potential of Erastin and its derivatives for endometriosis (EMS) by integrating mechanistic, preclinical, and translational perspectives. We conducted a focused review of literature from PubMed and Web of Science Core Collection (WoSCC) through August 2025; following a systematic screening and de-duplication process, 91 studies were included for synthesis. The evidence indicates that within the iron-rich, ROS-prone microenvironment of EMS, Erastin inhibits the system Xc− transporter, depletes intracellular glutathione (GSH), and inactivates GPX4, thereby driving ferroptosis in ectopic endometrial stromal cells. This process engages a coordinated network of regulated cell death that extends beyond ferroptosis to include crosstalk with necroptosis and pyroptosis, while being critically modulated by ferritinophagy and the paradoxical role of defective mitophagy. Despite the development of next-generation analogs with improved pharmacological properties, clinical translation is constrained by a narrow therapeutic window due to on-target and off-target toxicities. To overcome these limitations, we propose that future strategies must prioritize lesion-focused drug delivery, such as nanocarriers and triggerable prodrugs, alongside biomarker-guided treatment regimens to decouple efficacy from systemic risk, paving a credible path for the clinical application of Erastin-class agents in EMS.